Strategic Lawsuits Against Public Participation (SLAPP) - Kavaliauskaitė, Justė (Teisė, 2024)
To raise public awareness and draw attention to the pressing social, political, and economic problems, journalists, social activists, and NGO representatives often expose the non-transparent actions of stakeholders, the damage caused to society, etc. As a result, stakeholders initiate fictitious abusive proceedings against the entities, against which it is difficult to defend oneself. In this context, the subject of this paper is the essence of the SLAPP process. The aim of the work is to bring the topic of SLAPPs into the Lithuanian academic debate for the first time and to analyze the essence, characteristics, causes and objectives of SLAPPs. The article analyses the origins of SLAPP in the Anglo-Saxon law countries and the further development of SLAPP in Europe.The analysis of the doctrine and jurisprudence makes it possible to identify that SLAPP suits are aimed at intimidating the defendant and stopping the processes the subject has initiated, such as the dissemination of information of public interest. Defendants in this type of cases in Europe are usually media-related entities (journalists, bloggers, daily newspapers, etc.), social activists, NGOs, and lawyers.